Asked by  | 31st Jan, 2009, 09:29: PM

Expert Answer:

p and q are two zero so above equation can be written as  a(x-p)(x-q) so we have  p+q = -b/a and  pq = c/a ......by cmpairing two eqn. 

now  p2 + q2 = (p+q)2 - 2pq   ;   p3 + q3 = (p+q)3 - 3pq(p+q) ; and p4 + q4 =(p2 + q2)- 2p2q2 

using these relations we can get  the value of   a(p2/q + q2/p)+b(p3/q+q3/p) 

Answered by  | 31st Jan, 2009, 10:42: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.